Circumferential Rim Augmentation Suture Around the Perimeniscal Capsule Decreases Meniscal Extrusion and Progression of Osteoarthritis in Rabbit Meniscus Root Tear Model. Issue 3 (March 2022) - Park, Do Young; Yin, Xiang Yun; Chung, Jun Young; Jin, Yong Jun; Kwon, Hyeon Jae; Lee, Ga bin; Park, Jin Ho; Min, Byoung-Hyun
Background: We recently analyzed the joint capsule adjacent to the medial meniscus and found that the perimeniscal joint capsule has collagen fiber orientation similar to that of circumferential meniscal fibers, potentially playing a role in preventing extrusion. Purpose: To analyze the meniscal extrusion prevention potential of the circumferential rim augmentation suture around the perimeniscal capsule in a rabbit root tear model and analyze the biomechanical function in a porcine cadaveric knee. Study Design: Controlled laboratory study. Methods: Rabbit medial meniscus root tear models were divided into 3 experimental groups: root tear, root tear and suture repair, and root tear and circumferential rim augmentation suture. As for the circumferential rim augmentation suture procedure, a suture was placed to circumscribe the outer rim of the medial meniscus and passed through bone tunnels located at the tibial insertion of each root. After 4 and 8 weeks, meniscal extrusion was analyzed by micro–computed tomography, gross morphology, and histologic analysis of the medial femoral cartilage. For biomechanical analysis, porcine knees were divided into groups similar to rabbit experiments. Tibiofemoral contact parameters were assessed using a pressure mapping sensor system after applying a load of 200 N on the knee joint. Results: The root tear and circumferential rim augmentation suture group showed less meniscal extrusion, less gap within the tear site, and less cartilage degeneration compared with other groups after 4 and 8 weeks of surgery in the rabbit root tear model. Biomechanical analysis showed the root tear and circumferential rim augmentation suture group had larger contact area and lower peak contact pressure compared with root tear and root tear and suture repair groups. Conclusion: The circumferential rim augmentation suture reduced the degree of meniscal extrusion while restoring meniscal function, potentially preventing progression of arthritis in a rabbit root tear model and porcine knee biomechanical analysis. Clinical Relevance: The circumferential rim augmentation suture may be a novel augmentation option during root tear treatment.